Multiculturalism and feminist concerns in South Asian diaspora novels - Asim Karim,; Zakia Nasir, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The importance of multiculturalism within the parameters of feministic theory has become a new element for South Asian diaspora writers. They are keenly interested in debating the issues of cultural conflicts, differences, identity, assimilation, integration, negation, oppression, sex discrimination and gender inequality in their works. This paper with a focus on Monica Ali’s Brick Lane, Nadeem Aslam’s Maps for Lost Lovers brings out the features of female oppression that lead to their fragmentation on emotional, social, cultural and physical levels. Thus the focus of this paper is to analytically perceive how some prominent writers have shown feminist concerns about these situations.